Structural Negligence and State Harm in Public Safety: The Kelingking Beach Case - Wijaya, Louis O (UI Scholars Hub, 2026)
Kelingking Beach in Nusa Penida, Bali, is a highly promoted tourist destination that has been repeatedly associated with serious injuries and fatalities. Despite well-known hazards, incidents continue to occur, raising concerns about public safety governance at natural tourism sites. This study adopts a qualitative case study approach using media reports, policy statements, scientific studies on coastal risk management, and official tourism safety communications. Data were analyzed thematically to identify patterns of risk recognition, safety intervention, and institutional response. The findings reveal a recurring pattern of fatal and serious incidents at Kelingking Beach. Risk management has primarily relied on ambiguous signage, verbal advisories, and post-incident rescue efforts, while preventive structural mitigation and enforcement remain limited. Official responses tend to emphasize individual non-compliance rather than institutional responsibility. Recurring harm at Kelingking Beach reflects routine governance practices consistent with structural negligence, in which foreseeable risks are tolerated through institutional omission. Strengthening proactive and enforceable safety governance is essential to prevent foreseeable and avoidable public harm in tourism settings.